MPV17‐related mitochondrial DNA maintenance defect: New cases and review of clinical, biochemical, and molecular aspects. Issue 4 (13th January 2018) - El‐Hattab, Ayman W.; Wang, Julia; Dai, Hongzheng; Almannai, Mohammed; Staufner, Christian; Alfadhel, Majid; Gambello, Michael J.; Prasun, Pankaj; Raza, Saleem; Lyons, Hernando J.; Afqi, Manal; Saleh, Mohammed A. M.; et al.
Abstract: Mitochondrial DNA (mtDNA) maintenance defects are a group of diseases caused by deficiency of proteins involved in mtDNA synthesis, mitochondrial nucleotide supply, or mitochondrial dynamics. One of the mtDNA maintenance proteins is MPV17, which is a mitochondrial inner membrane protein involved in importing deoxynucleotides into the mitochondria. In 2006, pathogenic variants in MPV17 were first reported to cause infantile‐onset hepatocerebral mtDNA depletion syndrome and Navajo neurohepatopathy. To date, 75 individuals with MPV17 ‐related mtDNA maintenance defect have been reported with 39 different MPV17 pathogenic variants. In this report, we present an additional 25 affected individuals with nine novel MPV17 pathogenic variants. We summarize the clinical features of all 100 affected individuals and review the total 48 MPV17 pathogenic variants. The vast majority of affected individuals presented with an early‐onset encephalohepatopathic disease characterized by hepatic and neurological manifestations, failure to thrive, lactic acidemia, and mtDNA depletion detected mainly in liver tissue. Rarely, MPV17 deficiency can cause a late‐onset neuromyopathic disease characterized by myopathy and peripheral neuropathy with no or minimal liver involvement. Approximately half of the MPV17 pathogenic variants are missense. A genotype with biallelic missense variants, in particular homozygous p.R50Q, p.P98L, and p.R41Q, can carry a relatively better prognosis. Abstract : MPV17 is a mitochondrial inner membrane protein involved in importing deoxynucleotides into the mitochondria. To date, 75 individuals with MPV17 ‐related mitochondrial DNA (mtDNA) maintenance defect have been reported with 39 different MPV17 pathogenic variants. In this report, we present an additional 25 affected individuals with 9 novel MPV17 pathogenic variants. The vast majority of affected individuals presented with an early‐onset encephalohepatopathic disease. Rarely, MPV17 deficiency can cause a late‐onset neuromyopathic disease with no or minimal liver involvement.